2014
DOI: 10.1080/14634988.2014.875444
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effects of plerocercoid larvae of Ligula intestinalis (Cestoda) on Engraulicypris sardella (Cyprinidae) from northern Lake Nyasa/Malawi/Niasa

Abstract: Engraulicypris sardella (Günter, 1868) is a cyprinid fish exploited in the waters of Lake Nyasa that has been found to be infested by Ligula intestinalis (Linnaeus, 1758). Although L. intestinalis has been the subject of a number of studies, there is no information on the effects of this parasite on E. sardella. This study was therefore aimed at assessing the prevalence and intensity of the parasite L. intestinalis, condition of the fish and impact on fecundity of E. sardella. Data recorded for each individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…At low prevalence and infection rates, it is unclear whether this parasitic castration has any tangible ecological effects. Moreover, condition factor was not influenced by infection (Msafiri et al 2014), confirming that Ligula at low infection rates is relatively harmless (Ergonul and Altindag 2005). This also suggests that the loss of weight of the gonad is almost exactly compensated by abundance of perivisceral fat in the fish (Trubiroha et al 2010).…”
Section: Discussionmentioning
confidence: 71%
“…At low prevalence and infection rates, it is unclear whether this parasitic castration has any tangible ecological effects. Moreover, condition factor was not influenced by infection (Msafiri et al 2014), confirming that Ligula at low infection rates is relatively harmless (Ergonul and Altindag 2005). This also suggests that the loss of weight of the gonad is almost exactly compensated by abundance of perivisceral fat in the fish (Trubiroha et al 2010).…”
Section: Discussionmentioning
confidence: 71%
“…In Lake Nyasa this cestode has been increasingly reported since it was first noted by Mwambungu et al (1996).E. sardella appears to be the only species used as intermediate fish host (Msafiri et al , 2014;Rusuwa et al , 2014;Gabagambi and Skorping, 2018;Gabagambi et al , 2019) Figure S1). L. intestinalis is known to induce castration in several intermediate hosts (Wyatt and Kennedy, 1988;Kennedy et al , 2001;Loot et al , 2002;Cowx et al , 2008;Hoole et al , 2010) and has therefore been suggested to cause population crashes of its host (Burrough et al , 1979;Kennedy et al , 2001).…”
Section: Introductionmentioning
confidence: 95%
“…In infected fish the parasite is found filling the body cavity (Hooleet al , 2010). Higher infection rates are observed in larger and older E. sardella than in juvenile individuals (Msafiri et al , 2014;Rusuwa et al , 2014), which can partly be explained by diet shifts from phytoplankton to zooplankton as E. sardellareaches maturity.…”
Section: Introductionmentioning
confidence: 99%
“…Higher infection rates are observed in larger and olderE. sardella than in juvenile individuals (Msafiri et al, 2014;Rusuwa et al, 2014), which can be explained by diet shifts from phytoplankton to zooplankton as E. sardella reach maturity.…”
Section: The Parasitementioning
confidence: 99%
“…Ligula intestinalis (L. 1758) is a common and widespread cestode, that use cyprinid fish as intermediate hosts (Dubinina, 1980). In Lake Nyasa this cestode has been increasingly reported since it was first noted by Mwambungu et al (1996), where it infects the endemic pelagic fish Engraulicypris sardella ( Figure 1) (Gabagambi et al, 2019;Gabagambi and Skorping, 2018;Msafiri et al, 2014;Rusuwa et al, 2014). L. intestinalis is known to induce castration in several intermediate hosts (Cowx et al, 2008;Hoole et al, 2010;Kennedy et al, 2001;Loot et al, 2002;Wyatt and Kennedy, 1988) and has therefore been suggested to cause population crashes of its host (Burrough et al, 1979;Kennedy et al, 2001).…”
Section: Introductionmentioning
confidence: 97%